Effect of Relative Intensity Noise in Optical Transmission Systems Employing Wavelength Conversion Based on XPM and MZI - Hiew, C. C.; Abbou, F. M.; Chuah, Hean Teik (Taylor and Francis Online, 2005)
The overall intensity noise spectrum due to laser relative intensity noise (RIN) and interferometric conversion of laser phase noise after passing through wavelength conversion (WC) based on cross-phase modulation (XPM) and Mach-Zehnder interferometer (MZI) is modeled along with the resulting noise at the direct-detection receiver It is found that the effect of the laser-induced noise at the receiver is negligible when the MZI operated at quadrature and has a free spectral range (FSR) > 0.01 GHz. Only when FSR < 0.01 GHz is a power penalty induced that increases with decreasing laser current bias, j(0) (0.8 dB, j(0) = 2; 1.7 dB, j(0) = 1.5; 5.2 dB, j(0) = 1.1).